Hand hygiene, health care workers, methicillin-resistant Staphylococcus aureus, nosocomial infection, Staphylococcus aureus - Gunadi, Julius; Sastramihardja, Herri S.; Dewi, Nina Susana (Althea Medical Journal, 2015)
Background: Hypercholesterolemia is a major risk factor for coronary heart disease. Ear fungus (AuriculariaÂ auricula) contains soluble fiber (beta glucan) which is believed to have an effect of reducing cholesterolÂ level. The aim of this study was to determine the effect of fungus infusion in reducing blood cholesterol.Methods: This study used the laboratory experimental method conducted in the pharmacology laboratoryÂ of Dr. Hasan Sadikin General Hospital Bandung. The subjects were 25 male Wistar rats which were randomlyÂ divided into 5 groups. The first group was given only distilled water as a negative control, the remainingÂ groups were induced to be dyslipidemic and received fungus infusion with different doses of 18%, 36%,Â 72% and one group received no treatment.Results: The comparison of different doses showed all had the effect of reducing cholesterol levels comparedÂ to the positive control group (p<0.05). Each dose showed slight differences in their effectiveness, 18%Â (p=0.007; p<0.05), 36% (p=0.002; p<0.05), and 72% (p=0.014; p<0.05).Conclusions: ear fungus infusion had the effect of reducing cholesterol with the most effective concentrationÂ was 36%. [AMJ.2015;2(1):153â61]